THE DIFFERENCE OF KNOWLEDGE LEVEL OF MARKETING STAFF AND EMPLOYEES OF RSI UNISMA MALANG BETWEEN BEFORE AND AFTER BASIC MARKETING PRINCIPLE TRAINING - Damayanti, Yulia; Koeswo, Mulyatim; Sarwiyata, Tri Wahyu (Universitas Brawijaya, Indonesia, 2018)
This study is aimed to discover the result of training towards the difference of basic marketing principles knowledge between pre and post training in marketing staff and employees of RSI Unisma Malang. The method used was experimental or pre-post designed study, i.e. investigators performed an intervention; a training about basic marketing principles for marketing staff and employees of RSI Unisma Malang (32 people), hereafter compared the results between pre and post training. Results compared were scores obtained from pre-test before the participants got the training modules, and scores obtained after training. Data analysis used was the descriptive comparative approach, continued with paired t-test statistical analysis. Results obtained from pre-test, the average score was 7.63, lowest score was 5 and highest was 10, meanwhile from post-test, the average score was 9.22, lowest score was 8 and highest was 10, margin of error ï‚£ 2 from 20 people (62.5%) in pre-test and improved into 32 people (100%) in post-test. Result for paired sample t-test showed p value = 0.000, or <0.05 (ï¡). According to the elucidation above, we conclude that thereâ€™s a significant difference between before and after training, in other words, thereâ€™s a significant improvement in knowledge of basic marketing principles after training.